Find the sum or difference (5b-9)-3(8-2b)
2 answers:
-3(8-2b) -24 + 6b + 5b - 9 -15b + 11b. Can also be expressed as 11(b - 3)
<span>Simplifying
(5b + -9) + -3(8 + -2b) = 0
Reorder the terms:
(-9 + 5b) + -3(8 + -2b) = 0
Remove parenthesis around (-9 + 5b)
-9 + 5b + -3(8 + -2b) = 0
-9 + 5b + (8 * -3 + -2b * -3) = 0
-9 + 5b + (-24 + 6b) = 0
Reorder the terms:
-9 + -24 + 5b + 6b = 0
Combine like terms: -9 + -24 = -33
-33 + 5b + 6b = 0
Combine like terms: 5b + 6b = 11b
-33 + 11b = 0
Solving
-33 + 11b = 0
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '33' to each side of the equation.
-33 + 33 + 11b = 0 + 33
Combine like terms: -33 + 33 = 0
0 + 11b = 0 + 33
11b = 0 + 33
Combine like terms: 0 + 33 = 33
11b = 33</span>
You might be interested in
A.) x+4+x=20 should be the answer
Answer:
Step-by-step explanation:
4/5 is less than 1, so multiplying 5/8 by 4/5 results in a product smaller than the two factors.
Answer:
y = 375 + 90x is the equation
Answer:
The answer is $668.00
Step-by-step explanation:
Just add 200 to how much you will pay over time. So first multiply 39 by 12 (12 months in a year, 39 per month,) to find out how much you will pay by the end of the year then add 200 to that.
So, we have the information: Save $10 first month $5 the next months X = amount of months Cost = 175 So, it will take 7 months. 10+15+20+25+30+35+40 = 175